2018
DOI: 10.3389/fnmol.2018.00080
|View full text |Cite
|
Sign up to set email alerts
|

The Regulatory Mechanisms and Therapeutic Potential of MicroRNAs: From Chronic Pain to Morphine Tolerance

Abstract: Chronic pain, including cancer-related pain, is a pain condition often caused by inflammation or dysfunctional nerves. Chronic pain treatment poses a significant health care challenge, where opioids especially morphine are widely used and patients often develop tolerance over time with aggravated pain. microRNA (miRNA) is known to play important roles in regulating gene expressions in the nervous system to affect neuronal network plasticity related to algogenesis and the developing of morphine tolerance. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 125 publications
(145 reference statements)
1
27
1
Order By: Relevance
“…Anti‐miRNAs and miRNA mimics might be considered to reverse neuropathic pain (reviewed by Dai et al . ).…”
Section: Endogenous Triggersmentioning
confidence: 97%
See 1 more Smart Citation
“…Anti‐miRNAs and miRNA mimics might be considered to reverse neuropathic pain (reviewed by Dai et al . ).…”
Section: Endogenous Triggersmentioning
confidence: 97%
“…Therefore, miRNA emerged as a dynamic and endogenous axis of modulating neuronal excitability, independent of their effect on modulating gene expression. Anti-miRNAs and miRNA mimics might be considered to reverse neuropathic pain (reviewed by Dai et al [219]).…”
Section: Exosomementioning
confidence: 99%
“…Although many miRNAs are abnormally expressed in chronic pain and morphine tolerance, few miRNAs overlap. Dai et al (2018) found that only one miRNA (miR-124) was deregulated in microglia in NPP and morphine tolerance. Therefore, miR-124-based treatment is an important potential treatment.…”
Section: Mirnasmentioning
confidence: 99%
“…miRNAs have emerged as important players in posttranscriptional control of neuronal plasticity (Z. Hu & Li, ). miRNA modulation has also emerged as a new source of possible pain therapeutics (Table ; Dai et al, ; Lopez‐Gonzalez, Landry, & Favereaux, ). For example, knockdown of miRNA 155 has anti‐hyperalgesic effects in a neuropathic pain model (Liu, Zhu, Sun, & Xie, ).…”
Section: Rna Therapeutics Directed Against Mrnamentioning
confidence: 99%